Regulating the d-band center of Ru/CoMoO4 ternary heterostructure by interface engineering for accelerated hydrogen adsorption kinetics - Miao Ma; Min Yang; Cai-Yue Zhang; Hai-Yi Sun; Rong-Jing Su; Xiao-Rui Yue; Chen-Xi Li; Yong-Ming Chai; Bin Dong (Fuel, 2026)

Arginine-rich hemp seed globulin-tannic acid non-covalent complexation: Structural compaction, enhanced antioxidant/emulsifying properties, and modulated digestibility - Yu Zhang; Xiao-Dong Tian; Zuo-Xing Di; Hai-Bo Jin; Guang-Xiang He; Suo-He Yang; Rong-Yue Zhang; Lei Ma; Xiao-Yan Guo; Peng-Wei Xu (Food Chemistry, 2026)

Knockout of Resilin-like genes results in diminished wing size in silkworm moths - Tingting Tian; Chunxia Xiao; Haonan Dong; Qinglang Wang; Jia Fang; Zhonghui Dong; Yiran Zhu; Qingyu Rong; Yong Hou (Journal of Insect Physiology, 2026)

In-situ generation and activation of H2O2 by synergistic dipole moment and multi-metal cycle for piezo-photocatalytic water cleanup - Zheng-Tao Dong; Long Sui; You Wu; Xiao-Ju Wen; Ya-Ya Yang; Yan-Rong Chen; Wen-Jun Wang; Hai Guo (Chemical Engineering Journal, 2026)

Role of pyroptosis in melanoma: Molecular mechanisms and therapeutic potentials - Xiao-Han Zhang; Ke Zhang; Xue-Chun Qu; Jing Zhang; Umm E. Laila; Bo Wang; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Functional characterization of the MdMYB73L gene in drought and salt stress tolerance in apple - Xiao-Wen Li; Han-Yu Dong; Ya-Qi Liu; Jing-Yi Su; Xue Wang; Chang Li; Qi-Fei Wu; Wen-Xian Zhang; Xin-Rong Shi; Hong-Jian Cao; Qiangbo Liu; Xiao-Fei Wang; et al. (Plant Molecular Biology, 2026)

Integrated metabolomic and transcriptomic analyses reveal that pectin metabolism mediates texture divergence in grape berries - Zhi-Meng Gan; Xiao-Yan Ai; Yong Liu; Wei Zhu; Yang Zhang; Hui-Liang Wang; Fu-Rong Wang; Xiao-Dong Hou; Hua-Ping He; Lin-Zhong Gong (Postharvest Biology and Technology, 2026)

Latitudinal gradients shape adaptive divergence of tea saponin accumulation in Camellia oleifera - Danmei Yu; Liyun Feng; Suyun Zhang; Xiaohua Liu; Huan Yang; Jie Xiao; Shang Chen; Xia Dong; Li Cheng; Yao Zhao; Jun Rong; Jian Zhang (Food Bioscience, 2026)

Cholesteryl ester accumulation as a biomarker for personalized selection of fertility-preserving therapies in endometrioid endometrial carcinoma - Yijiao He; Shenyi Yin; Wenying Zhao; Yanmin Wang; Danhua Shen; Yi Wang; Jing Geng; Xiaobo Zhang; Ying Yu; Juan Li; Yang He; Jiaxin Li; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Ganoderma lucidum spore lipid extract synergizes with chemotherapy to alleviate tumor progression by enhancing macrophage phagocytosis of dying tumor cells - Guan-Di Xiao; Zi-Xuan Li; Yi-Fang Li; Lei Liang; Cheng Yuan; Wen-Dong Xu; Ju-Yan Liu; Yan-Ping Wu; Rong-Rong He (PharmaNutrition, 2026)

A germline-specific vesicular structure licenses mRNA activation during spermiogenesis and is hijacked in gastric cancer - Mingxi Liu; Zerui Wang; Yinuo Li; Qingsong Xie; Zhuang Xiao; Xuezhi He; Guanxiong Wang; Yang Gao; Yini Zhang; Lin Zheng; Xun Xia; Lujie Chen; et al. (Science Bulletin, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

Antifungal mechanisms of Bacillus velezensis Shannan.BV80-12 extracellular metabolites against the citrus postharvest pathogen Penicillium italicum - Rong Wang; Yali Tan; Feiyan Dong; Jiao Yang; Xiao Li; Tong Gu; Jialan Zhang; Li Li; Mengxiang Gao (Postharvest Biology and Technology, 2026)

Local electric field regulation induces specific catalysis to achieve efficient and selective sensing of methanol - Cundong Feng; Shizhu Ling; Rong Tan; Weian Du; Xueqin Ouyang; Jianjun Xiong; Yangfeng Li; Haoyang Ren; Yingpu Wang; Weifang Liao; Qian Xiao; Wentao Dong; et al. (Chemical Engineering Journal, 2026)

Stage-specific ion release from dual-crosslinked alginate/boron-doped bioactive glass hydrogel accelerates infected wound healing - Fuqiang Song; Linyuan Jiang; Anqi Ye; Rong Huang; Anwen Lai; Longyang Xu; Wei Shen; Junjun Li; Jiayan Hui; Andi Suo; Yanzhi Xiong; Xiaoyu Dong; et al. (Carbohydrate Polymers, 2026)

One-step phase separation and magnetic retrieval of switchable natural deep eutectic solvents via Fe3O4@CA composites for rapid extraction of illegal non-steroidal anti-inflammatory drugs in herbal extracts - Jin-Yue Dong; Rong-Jie Wang; Qing Ran; Xiao-Bei Yang; Wen-Chao Han; Feng-Qi Dong; Di Chen (Sustainable Chemistry and Pharmacy, 2026)

Predicting the kinetics of Cu release and transport in contaminated soils in the field - Liang Dong; Rong Li; Wenxia Wang; Zhifang Xiao; Zezhen Ren; Qianting Ye; Zhenqing Shi (Applied Geochemistry, 2026)

Juvenile-Onset Cerebrotendinous Xanthomatosis with Novel Compound Heterozygous CYP27A1 Mutations: Case Series and Literature Review - Kefang Du; Chunrong Wang; Linlin Wan; Zhao Chen; Hongyu Yuan; Qian Jiang; Xiao Dong; Daji Chen; Riwei Ouyang; Xiafei Long; Xiaokang Wu; Xinying Xiao; et al. (The Cerebellum, 2026)

Microbial processing of organic matter in cold seep sediments revealed by amino compound distributions and degradation indices - Yang Wu; Lina Lyu; Meiqing Lin; Shengtao Ma; Cheng Yang; Rong Wu; Kaiqin Huang; Xi Xiao; Yifei Dong; Binbin Guo; Danyi Su; Jing Zhao; et al. (Marine Pollution Bulletin, 2026)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

One new aryltetralin lignan and other components from Blachia pentzii - Yan-Yan Zhang; Feng-Cheng Zhang; Yue Zhang; Hong-Yan Yu; Hai-Rong Xu; Xiao-Yun Dong; Chang-Shui Yang (Phytochemistry Letters, 2025)

Engineering sulfoxide synthases for efficient microbial production of ergothioneine: Mechanisms, strategies, and perspectives - Xiaodi Wei; Lijuan Liu; Sheng Dong; Pingle Wu; Xiao Zhang; Min Yang; Rong Zheng; Haibo Zhang (Food Chemistry, 2025)

Construction of antibacterial-enhanced 2D ZnO@ZIF-8 nanocomposites based on synergistic antimicrobial mechanisms and application in maize long-term storage - Song-Yue Xu; Chao-Shuai Mei; Ke-Yu Zhou; Feng Xiao; Min Zhang; Qiong Wu; Yu-Rong Zhang; Dong-Dong Zhang (Food Chemistry, 2025)

Investigation of the Shallow Structure of the Hami Basin Northern Margin Fault Using Comprehensive Geophysical Methods - Guang-hong Ju; Xiao-dong He; Rong-ying Zheng; Yan-ling Liu; Jun-qi Duan; Jun Shen; Zhi-tao Gao (Applied Geophysics, 2025)

AIEgen-based porous organic polymer-Ag nanoparticles hybrids with coreaction accelerator amplification and covalent rigidification-enhanced electrochemiluminescence for aflatoxin M1 detection - Jun-Qi Song; Qiu-Yi Peng; Mei-Ling Lu; Shu-Zhen Gao; Wen-Bin Liang; Shaoguang Sun; Ruo Yuan; Dong-Rong Xiao (Food Chemistry, 2025)

Novel pyrene-based metal-organic framework nanosheets' metal ions directly serve as coreaction accelerators to boost their electrochemiluminescence performance for fabricating supersensitive biosensor - Qiu-Yi Peng; Qiu-Yue Li; Yang Yang; Jun-Qi Song; Bing-Ling Yu; Wen-Bin Liang; Yan Li; Ruo Yuan; Dong-Rong Xiao (Chemical Engineering Journal, 2025)

Daily temperature fluctuations intensify the toxicokinetics and toxicodynamics of phenanthrene in Enchytraeus albidus (Oligochaeta), increasing overall toxicity risk - Naichuan Xiao; Ming Gao; Dong Zhu; Zifang Wang; Rong Huang; Lelin You; Tingting Zhang; Wencai Dai (Journal of Hazardous Materials, 2025)

Ten eudesmane sesquiterpenoids from Dobinea delavayi and their antimalarial and lipid-lowering activities - Wei Chen; Li-Tian Dong; Pei-Mi He; Wei-Juan Zu; Yi-Ling Yang; Rong Liu; Bei Jiang; Chao-Jiang Xiao (Phytochemistry, 2025)

Genome-wide association and epidemiological evidence linking air pollution to aging mechanisms - Xiao-Yu Liu; Dong Peng; Xu-Rui Liu; Yuan-Hui Sheng; Jun-Nan Zhao; Rong-Bin Xu; Dan Zhang; Bo Chen (Journal of Hazardous Materials, 2025)

Bridging the knowledge gap: From poly(butylene adipate-co-terephthalatebutylene) degradation to CO2-generating mineralization under the synergistic effect of bacteria and fungi - Yue Wang; Qi Liu; Chang-Hong Xie; Ruo-Tong Zhao; Qiu-Xiang Tang; Dong-Fei Han; Yi-Ning Xia; Ji-Xiao Cui; Chang-Rong Yan; Wen-Qing He (Journal of Hazardous Materials, 2025)

MilTilV: a vertically resolved microbial explicit soil organic carbon turnover model integrated the effect of tillage operation - Kaihao YE; Liang DONG; Yijin LV; Wenxia WANG; Zhifang XIAO; Junran LI; Zhenqing SHI; Rong LI (Pedosphere, 2025)

Transitional chromitites within the Maqsad crust-mantle transition zone of the Semail ophiolite formed above the nascent forearc setting - Rong-Zhong Bo; Peng-Jie Cai; Dong-Yang Lian; Jing-Sui Yang; Sobhi Nasir; Hui-Chao Rui; Yu-Xiao Lu; Chu-Qi Cao; Ahmed E. Masoud (Lithos, 2025)

Ambient air pollution and the risk of cancer: Evidence from global cohort studies and epigenetic-related causal inference - Dong Peng; Xiao-Yu Liu; Yuan-Hui Sheng; Si-Qi Li; Dan Zhang; Bo Chen; Pei Yu; Zhao-Yuan Li; Shuai Li; Rong-Bin Xu (Journal of Hazardous Materials, 2025)

Bismuth tungstate/graphite carbon nitride composites for efficient photocatalytic reduction of U(VI): Synthesis, performance, and mechanism - Yu-Jia Xiao; Shi Chen; Ping Li; Dong Zhang; Jing-Jing Wang; Hui Dong; Yan-Rong He (Journal of Environmental Chemical Engineering, 2025)

Iron isotopic fractionation during seafloor hydrothermal alteration of oceanic upper crust, as recorded in Geotimes lavas of Semail ophiolite, Oman - Rong-Zhong Bo; Yildirim Dilek; Wei-Qiang Li; Sobhi Nasir; Peng-Jie Cai; Hui-Chao Rui; De-Hong Du; Shi-Chao An; Yu-Xiao Lu; Hao-Chen Duan; Dong-Yang Lian; Jing-Sui Yang; et al. (Chemical Geology, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Hydroxysafflower yellow A alleviates the inflammatory response in astrocytes following cerebral ischemia by inhibiting the LCN2/STAT3 feedback loop - Lijuan Song; Yige Wu; Lijun Yin; Yanzhe Duan; Jianlin Hua; Mengwei Rong; Kexin Liu; Junjun Yin; Dong Ma; Ce Zhang; Baoguo Xiao; Cungen Ma (Metabolic Brain Disease, 2025)

Toxic aldehydes in fried foods: Formation, analysis, and reduction strategies - Xing-yang Guo; Liang-yu Cheng; Chao Chang; Xiao-ming Jiang; Pan Gao; Wu Zhong; Chuan-rong Hu; Dong-ping He; Jiao-jiao Yin (Food Control, 2025)

Drug–drug interaction of phenytoin sodium and methylprednisolone on voriconazole: a population pharmacokinetic model in children with thalassemia undergoing allogeneic hematopoietic stem cell transplantation - Yun Wu; Lu-lu Niu; Ya-yun Ling; Si-ru Zhou; Tian-min Huang; Jian-ying Qi; Dong-ni Wu; Rong-da Cai; Ting-qing Wu; Yang Xiao; Taotao Liu (European Journal of Clinical Pharmacology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

The Role of the Intestinal Flora and Its Derivatives in Neurocognitive Disorders: A Narrative Review from Surgical Perspective - Jian Huang; Tian-Shou Qin; Yun Bo; Yu-Jin Li; Rong-Sheng Liu; Yang Yu; Xiao-Dong Li; Jin-Can He; Ai-Xin Ma; Da-Peng Tao; Wen-Jun Ren; Jun Peng (Molecular Neurobiology, 2025)
Perioperative neurocognitive dysfunction is a significant concern for population health, impacting postoperative recovery and increasing the financial burden on patients. With an increasing number of surgical procedures being performed, the prevention and management of perioperative neurocognitive dysfunction have garnered significant attention. While factors such as age, lifestyle, genetics, and education are known to influence the development of cognitive dysfunction, recent research has highlighted the role of the gut microbiota in neurological health. An increased abundance of pro-inflammatory gut microbiota can trigger and worsen neuroinflammation, neuronal cell damage, and impaired cellular autophagy. Moreover, the inflammation-promoting gut microbiota can disrupt immune function, impair neuroautophagy, and affect the production and circulation of extracellular vesicles and neurotransmitters. These factors collectively play a role in the onset and advancement of cognitive impairment. This narrative review delves into the molecular mechanisms through which gut microbiota and their derivatives contribute to cognitive impairment, focusing on the impact of anesthesia surgery, changes in gut microbial populations, and perioperative cognitive impairment associations. The study suggests that alterations in the abundance of various bacterial species and their metabolites pre- and post-surgery may be linked to postoperative cognitive impairment. Furthermore, the potential of probiotics or prebiotics in addressing cognitive impairment is discussed, offering a promising avenue for investigating the treatment of perioperative neurocognitive disorders.

Effect of Maillard reaction on the allergenicity of crude extract of Mactra quadrangularis - Fa-Jie Li; Xin-Rong He; Dong-Xiao Li; Yang Yang; Shuai Kang; Qing-Mei Liu; Lian-Zhong Luo; Gui-Xia Chen; Guang-Ming Liu (Food Research International, 2025)

Fast detection of NO2 by In2O3@ZnO nanofibers synthesized by coaxial electrospinning: Real-time monitoring application of smart mask - Xingyu Kang; Haibo Yu; Xiao Ma; Eryang Shang; Hong Chen; Huizhang Zhao; Jiawei Zhang; Rong Tan; Dong Wang; Hairui Fang (Chemical Engineering Journal, 2025)

Partial organic substitution increases soil quality and crop yields but promotes global warming potential in a wheat-maize rotation system in China - Gong Wu; Hai-meng Huang; Bei-bei Jia; Lei-lei Hu; Chong-sheng Luan; Qi Wu; Xiao-yu Wang; Xiao-xiao Li; Zhao Che; Zhao-rong Dong; He Song (Soil and Tillage Research, 2024)

β-Caryophyllene oxide inhibits lysine acetylation of histones in Fusarium proliferatum to block ribosomal biosynthesis and function - Hong-Xin Liao; Jing Yang; Jin-Rui Wen; Hong-Yan Nie; Jun Zhao; Fu-Rong Xu; Xiao-Yun Liu; Xian Dong (Pesticide Biochemistry and Physiology, 2024)

Chemical constituents from noni (Morinda citrifolia L.) fruit juice and their chemotaxonomic significance - Yu-Qin Meng; Bin Zhang; Dong-Hui Zhang; Zhang-Xin Yu; Chun-Hua Long; Si-Rong Li; Xue-Na Zhang; Xiao-Bao Li; Guang-Ying Chen (Biochemical Systematics and Ecology, 2024)

Correction: A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

Identification and performance of endophytic actinobacteria Ahn65 with functions of growth promotion and disease resistance for rice - Hua Yang; Zhan Hu; Rong Xiao; Zhu-dong Liu; Min Zhang; Yi-Lu Li; Shan-dong Wu; Zu-jiao Fu (Physiological and Molecular Plant Pathology, 2024)

Molecularly tailored bifunctional nano-overlayers for efficient and stable inverted perovskite solar cells - Lu-Lu Jiang; Shao-Jie Li; Qi Li; Shuai-Ke Guo; Zhen-Rong Song; Ying-Zhuo Shen; Xiao-Nan Zhang; Dong-Sheng Zheng; Xiao-Dan Tang; Hai-Rui Liu (Chemical Engineering Journal, 2024)

Experimental studies and pore-scale modeling of hydrate dissociation kinetics at different depressurization rates in a cubic hydrate simulator - Chang-Wen Xiao; Xiao-Sen Li; Hong-Feng Lu; Gang Li; Chen-Lu Xu; Rong-Rong Qi; Dong-Hui Xing; Xian Li; Yi-Fan Weng; Lu Yu (Chemical Engineering Journal, 2024)

Gene expression profiles and metabolic pathways responsible for male sterility in cybrid pummelo - Rong Wang; Yang-Cao Shi; Bo Zhang; Wan-Rong Liu; Feng-Quan Tan; Fang Lu; Nan Jiang; Lai-Chao Cheng; Kai-Dong Xie; Xiao-Meng Wu; Wen-Wu Guo (Plant Cell Reports, 2024)

Evaluation of the safety, immunogenicity and protective effect of an attenuated Pseudomonas plecoglossicida strain ΔgacS as the live vaccine for the large yellow croaker (Larimichthys crocea) - Tian-Jing Kang; Su-Ming Zhou; Xiao Xie; Rong-Rong Ma; Dong Qian; Shan Jin; Fei Yin (Fish & Shellfish Immunology, 2024)

Preliminary analysis of the indicators and accumulation models of gas hydrates in the central Zhongjiannan Basin, western South China sea - Zhou-rong Cai; Xin Sui; Yong-jian Yao; Zheng-xin Yin; Xiao-dong Yang; Dong Ju; Rong-wei Zhu; Xiao-xiang Wang; Huo-dai Zhang (Marine and Petroleum Geology, 2024)

A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Effect of topographic slope on the interaction between debris flows and riparian forests - Wen-rong Cui; Jian-gang Chen; Xiao-qing Chen; Dong-ri Song; Wan-yu Zhao; Ke Jin (Landslides, 2024)

Partial organic substitution for synthetic fertilizer improves soil fertility and crop yields while mitigating N2O emissions in wheat-maize rotation system - Gong Wu; Shuo Yang; Chong-sheng Luan; Qi Wu; Lei-li Lin; Xiao-xiao Li; Zhao Che; De-bao Zhou; Zhao-rong Dong; He Song (European Journal of Agronomy, 2024)

Rigidifying AIEgens in covalent organic framework nanosheets for electrochemiluminescence enhancement: TABE-PZ-CON as a novel emitter for microRNA-21 detection - Jin-Ling Zhang; Tian-Tian Wang; Wen-Bin Liang; Ruo Yuan; Dong-Rong Xiao (Analytica Chimica Acta, 2024)

Uranium speciation and distribution on the surface of Shewanella putrefaciens in the presence of inorganic phosphate and zero-valent iron under anaerobic conditions - Guo-Xiu Xuan; Guo-Hao Zhang; Wen-Cai Cheng; Chun-Yan Ma; Qing-Rong Li; En-Tong Liu; Wen-Ge He; Fa-Qin Dong; Xiao-An Li; Zheng-Guo Chen; Xiao-Qin Nie (Science of The Total Environment, 2024)

Two calcium-based metal organic frameworks with long afterglow as anticounterfeiting materials - Rong-Hui Shi; Zhi-Qiang Long; Fanan Wang; Ling-Zhu Gong; Xiao-Ying Lin; Gui-Lin Zhuang; Dong-Fei Lu (Chemical Engineering Journal, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

Soil pH differently affects N2O emissions from soils amended with chemical fertilizer and manure by modifying nitrification and denitrification in wheat-maize rotation system - Gong Wu; Fei Liang; Qi Wu; Xiao-Gang Feng; Wen-ding Shang; Hua-wei Li; Xiao-xiao Li; Zhao Che; Zhao-rong Dong; He Song (Biology and Fertility of Soils, 2024)

Effect comparisons of different conditioners and microbial agents on the degradation of estrogens during dairy manure composting - Yan Li; Dong Zeng; Xiao-Lu Jiang; De-Chun He; Jia-Wu Hu; Zi-Wei Liang; Jia-Cheng Wang; Wang-Rong Liu (Chemosphere, 2023)

Rapid and sensitive Cas13a/Cas12a-based one-pot dual-target strategy to detect monkeypox virus and its co-infected viruses - Xiao Wang; Qiao Rao; Zhengrong Lu; Xiaobao Deng; Rong Shen; Rui Wang; Weiyi Dong; Xianhua Qi; Zhen Jin; Youzhi Tang; Dan Du (Science Bulletin, 2023)

An integrative analysis of lipidomics and transcriptomics in various mouse brain regions in response to real-ambient PM2.5 exposure - Shuangjian Qin; Huixian Zeng; Qizhen Wu; Qingqing Li; Mohammed Zeeshan; Lizhu Ye; Yue Jiang; Rui Zhang; Xinhang Jiang; Miao Li; Rong Zhang; Wen Chen; et al. (Science of The Total Environment, 2023)

Effects of organic carbon/elemental carbon and particle size on inhalation bioaccessibility of particle-bound PAHs - Chun-Xue Tang; Ying Dong; Xiao-Yu Yuan; Rong Wang; Chen-Chou Wu; Lian-Jun Bao; Eddy Y. Zeng (Science of The Total Environment, 2023)

Daphnia magna uptake and excretion of luminescence‐labelled polystyrene nanoparticle as visualized by high sensitivity real-time optical imaging - Yu-Hang Zhang; Rong-Yao Gao; Ze-Jun Wang; Qian-Qian Shao; Ya-Wen Hu; Hua-Bing Jia; Xiao-Jing Liu; Feng-Qin Dong; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2023)

Nudifloids A-N, structurally diverse 3,4-seco-labdane diterpenoids from Callicarpa nudiflora with inflammatory inhibitory activity - Xue-Rong Zhao; Xiao-Rong Sun; Xing-Jie Zhang; Xue-Wen Wu; Bin Cheng; Dong-Xuan Ni; Jia-Bi Huang; Rui-Han Zhang; Xiao-Li Li; Wei-Lie Xiao (Phytochemistry, 2023)

A mathematical model for intracellular NO and ROS dynamics in vascular endothelial cells activated by exercise-induced wall shear stress - Xiao Zeng; Chun-Dong Xue; Yong-Jiang Li; Kai-Rong Qin (Mathematical Biosciences, 2023)

Four new phenolic glycosides from Dobinea delavayi - Xiu-Rong Wu; Li-Juan Lang; Yi Shen; Xiang Dong; Chao-Jiang Xiao; Bei Jiang (Natural Product Research, 2023)

Disinfection byproducts in indoor swimming pool water: Detection and human lifetime health risk assessment - Di Zhang; Shengkun Dong; Li Chen; Rong Xiao; Wenhai Chu (Journal of Environmental Sciences, 2023)

Programmable phthalocyanine-iron-based nanoreactor for fluorescence/magnetic resonance dual-modality imaging-guided sono/chemodynamic therapies - Dong Li; Jie Pan; Shuyu Xu; Bingwei Cheng; Shuaiying Wu; Qixuan Dai; Mei-Rong Ke; Bi-Yuan Zheng; Chengchao Chu; Chao Liu; Yang Zhang; Xiao Xu; et al. (Chemical Engineering Journal, 2023)

Infestation and distribution of chigger mites on Confucian white-bellied rat (Niviventer confucianus) in Southwest China - Yan-Ling Chen; Xian-Guo Guo; Wen-Yu Song; Tian-Guang Ren; Lei Zhang; Rong Fan; Cheng-Fu Zhao; Zhi-Wei Zhang; Wen-Ge Dong; Xiao-Bin Huang (Biologia, 2022)

Impact of heat stress on milk yield, antioxidative levels, and serum metabolites in primiparous and multiparous Holstein cows - Xue Chen; Jia Nan Dong; Ji Ye Rong; Jun Xiao; Wei Zhao; Natnael D. Aschalew; Xue Feng Zhang; Tao Wang; Gui Xin Qin; Zhe Sun; Yu Guo Zhen (Tropical Animal Health and Production, 2022)

Flavonoid glycosides from the nectar of Camellia reticulata Lindl. - Xin-Lan Chen; Xing-Rong Peng; Xue-Yang Gong; Yi-Qiu Liu; Zhuo Qing; Xiao-Xiao Ren; Rui Su; Li-Ming Fang; Ming-Hua Qiu; Kun Dong (Natural Product Research, 2022)

Apatite chemistry as a petrogenetic–metallogenic indicator for skarn ore-related granitoids: an example from the Daye Fe–Cu–(Au–Mo–W) district, Eastern China - Run-Jie Zhou; Guang Wen; Jian-Wei Li; Shao-Yong Jiang; Hao Hu; Xiao-Dong Deng; Xin-Fu Zhao; Dai-Rong Yan; Ke-Tao Wei; Heng-An Cai; Shi-Chao Shang; Bai-Cun Li; et al. (Contributions to Mineralogy and Petrology, 2022)

Pepsinogen C expression–related lncRNA/circRNA/mRNA profile and its co-mediated ceRNA network in gastric cancer - Li-rong Yan; Han-xi Ding; Shi-xuan Shen; Xiao-dong Lu; Yuan Yuan; Qian Xu (Functional & Integrative Genomics, 2021)

Neuroprotective Effect of Phthalide Derivative CD21 against Ischemic Brain Injury:Involvement of MSR1 Mediated DAMP peroxiredoxin1 Clearance and TLR4 Signaling Inhibition - Xiao Zou; Xiao-Jia Yang; Yu-Miao Gan; Dong-Ling Liu; Chu Chen; Wei Duan; Jun-Rong Du (Journal of Neuroimmune Pharmacology, 2021)

Isolation and Identification of Pseudomonas sp. Strain DY-1 from Agricultural Soil and Its Degradation Effect on Prometryne - Dong Liang; Ming-yue Ding; Chang-yixin Xiao; Ya-wen Shen; Yin-yue Wang; Hai-tao Li; Rong-mei Liu; Ji-guo Gao (Current Microbiology, 2021)

Phytoremediation of Cadmium Contaminated Soil: Impacts on Morphological Traits, Proline Content and Stomata Parameters of Sweet Sorghum Seedlings - Xicun Dong; Yan Chang; Rong Zheng; Xueqiang Wang; Xia Yan; Xiao-Fei Ma (Bulletin of Environmental Contamination and Toxicology, 2021)

Addition of oyster shell to enhance organic matter degradation and nitrogen conservation during anaerobic digestate composting - Ming-Yi Lu; Xiao-Shuang Shi; Xu Li; Shu-Juan Lian; Dong-Yan Xu; Rong-Bo Guo (Environmental Science and Pollution Research, 2020)

Release from below- and aboveground natural enemies contributes to invasion success of a temperate invader - Yuan-Zheng Zhao; Ming-Chao Liu; Yu-Long Feng; Dong Wang; Wei-Wei Feng; Keith Clay; Lekeah A. Durden; Xiu-Rong Lu; Shuo Wang; Xiao-Lin Wei; De-Liang Kong (Plant and Soil, 2020)

Characterization of Pingliang xiaoheidou (ZDD 11047), a soybean variety with resistance to soybean cyst nematode Heterodera glycines - Wei Guo; Jing S. Chen; Feng Zhang; Ze Y. Li; Hai F. Chen; Chan J. Zhang; Li M. Chen; Song L. Yuan; Rong Li; Dong Cao; Qing N. Hao; Shui L. Chen; et al. (Plant Molecular Biology, 2020)

Simulation of the landform change process on a purple soil slope due to tillage erosion and water erosion using UAV technology - Chao Yang; Zheng-an Su; Jian-rong Fan; Hai-dong Fang; Liang-tao Shi; Jian-hui Zhang; Zhou-yao He; Tao Zhou; Xiao-yi Wang (Journal of Mountain Science, 2020)

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Elevated Hs-CRP Levels Are Associated with Higher Risk of Intracranial Arterial Stenosis - Bing-Jie Su; Yi Dong; Chen-Chen Tan; Xiao-He Hou; Wei Xu; Fu-Rong Sun; Mei Cui; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Urinary Metal Concentrations and the Incidence of Hypertension Among Adult Residents Along the Yangtze River, China - Qi Zhong; Chun-xiao Jiang; Chi Zhang; Qian Zhang; Qi-rong Qin; Xiao-dong Wang; Fen Huang (Archives of Environmental Contamination and Toxicology, 2019)

Effect of Apolipoprotein E Genotypes on Huntington’s Disease Phenotypes in a Han Chinese Population - Xiao-Yan Li; Yan-Bin Zhang; Miao Xu; Hong-Rong Cheng; Yi Dong; Wang Ni; Hong-Lei Li; Zhi-Ying Wu (Neuroscience Bulletin, 2019)

Effects of NaCl stress on growth of Portulaca oleracea and underlying mechanisms - Jin-Cheng Xing; Jing Dong; Mao-Wen Wang; Chong Liu; Bao-Quan Zhao; Zhu-Gui Wen; Xiao-Mei Zhu; Hai-Rong Ding; Xiao-Hui Zhao; Li-Zhou Hong (Brazilian Journal of Botany, 2019)

In Vitro Susceptibility of Berberine Combined with Antifungal Agents Against the Yeast Form of Talaromyces marneffei - Hong Luo; Kai-su Pan; Xiao-lu Luo; Dong-yan Zheng; Alex Andrianopoulos; Le-min Wen; Yan-qing Zheng; Jing Guo; Chun-yang Huang; Xiu-ying Li; Rong Hu; Yu-jiao Li; et al. (Mycopathologia, 2019)

Relationship between polymorphisms of the lipid metabolism-related gene PLA2G16 and risk of colorectal cancer in the Chinese population - Xiao-Nv Xie; Jing Yu; Li-Hua Zhang; Zhi-Ying Luo; Dong-Sheng Ouyang; Ling-Jie Zheng; Chun-Yang Wang; Li Yang; Ling Chen; Zhi-Rong Tan (Functional & Integrative Genomics, 2019)

Studies of the Interaction of Influenza Virus RNA Polymerase PAN with Endonuclease Inhibitors - Li-hua Dong; Xiao-rong Cao (Interdisciplinary Sciences: Computational Life Sciences, 2018)

Spatial distribution of turbulent mixing in the upper ocean of the South China Sea - Xiao-Dong Shang; Chang-Rong Liang; Gui-Ying Chen (Ocean Science, 2017)
The spatial distribution of the dissipation rate (ε) and diapycnal diffusivity (κ) in the upper ocean of the South China Sea (SCS) is presented from a measurement program conducted from 26 April to 23 May 2010. In the vertical distribution, the dissipation rates below the surface mixed layer were predominantly high in the thermocline where shear and stratification were strong. In the regional distribution, high dissipation rates and diapycnal diffusivities were observed in the region to the west of the Luzon Strait, with an average dissipation rate and diapycnal diffusivity of 8.3 × 10−9 W kg−1 and 2.7 × 10−5 m2 s−1, respectively, almost 1 order of magnitude higher than those in the central and southern SCS. In the region to the west of the Luzon Strait, the water column was characterized by strong shear and weak stratification. Elevated dissipation rates (ε > 10−7 W kg−1) and diapycnal diffusivities (κ > 10−4 m2 s−1), induced by shear instability, occurred in the water column. In the central and southern SCS, the water column was characterized by strong stratification and weak shear and the turbulent mixing was weak. Internal waves and internal tides generated near the Luzon Strait are expected to make a dominant contribution to the strong turbulent mixing and shear in the region to the west of the Luzon Strait. The observed dissipation rates were found to scale positively with the shear and stratification, which were consistent with the MacKinnon–Gregg model used for the continental shelf but different from the Gregg–Henyey scaling used for the open ocean.

Association between hyperhomocysteinemia and stroke with atherosclerosis and small artery occlusion depends on homocysteine metabolism-related vitamin levels in Chinese patients with normal renal function - Guan-Hui Wu; Fan-Zhen Kong; Xiao-Feng Dong; De-Feng Wu; Qian-Zhu Guo; Ai-Rong Shen; Qing-Zhang Cheng; Wei-Feng Luo (Metabolic Brain Disease, 2017)

Lower functional connectivity of default mode network in cognitively normal young adults with mutation of APP, presenilins and APOE ε4 - Yun Yan Su; Xiao Dong Zhang; U. Joseph Schoepf; Akos Varga-Szemes; Andrew Stubenrauch; Xue Liang; Li Juan Zheng; Gang Zheng; Xiang Kong; Qiang Xu; Shou Ju Wang; Rong Feng Qi; et al. (Brain Imaging and Behavior, 2017)

Observations of the turbulent kinetic energy dissipation rate in the upper central South China Sea - Chang-Rong Liang; Gui-Ying Chen; Xiao-Dong Shang (Ocean Dynamics, 2017)

EGFL7-overexpressing epidermal stem cells promotes fibroblast proliferation and migration via mediating cell adhesion and strengthening cytoskeleton - Rong-Hua Yang; Shao-Hai Qi; Shu-Bin Ruan; Ze-Peng Lin; Yan Lin; Feng-Gang Zhang; Xiao-Dong Chen; Ju-Lin Xie (Molecular and Cellular Biochemistry, 2016)

DBOP specifies palea development by suppressing the expansion of the margin of palea in rice - Dong-Dong Zeng; Ran Qin; Md. Alamin; Rong Liang; Cheng-Cong Yang; Xiao-Li Jin; Chun-Hai Shi (Genes & Genomics, 2016)

Emerging role of adipokines in systemic lupus erythematosus - Hong-Miao Li; Tian-Ping Zhang; Rui-Xue Leng; Xiang-Pei Li; Xiao-Mei Li; Hai-Rong Liu; Dong-Qing Ye; Hai-Feng Pan (Immunologic Research, 2016)

A Fluorescence Immunochromatographic Assay Using Europium (III) Chelate Microparticles for Rapid, Quantitative and Sensitive Detection of Creatine Kinase MB - Xiao-Hong Lai; Rong-Liang Liang; Tian-Cai Liu; Zhi-Ning Dong; Ying-Song Wu; Lin-Hai Li (Journal of Fluorescence, 2016)

Genetic Diversity and Population Structure Patterns in Chinese Cherry (Prunus pseudocerasus Lindl) Landraces - Tao Chen; Xiao-jiao Huang; Jing Zhang; Qing Chen; Yin Liu; Hao-ru Tang; Dong-ming Pan; Xiao-rong Wang (Plant Molecular Biology Reporter, 2016)

Erratum to: An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2016)

Soil washing in combination with homogeneous Fenton-like oxidation for the removal of 2,4,4′-trichlorodiphenyl from soil contaminated with capacitor oil - Xiao-Hong Ma; Ling Zhao; Zhi-Rong Lin; Yuan-Hua Dong (Environmental Science and Pollution Research, 2016)

Erratum to: First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2016)

Lentibacillus amyloliquefaciens sp. nov., a halophilic bacterium isolated from saline sediment sample - Jing-Li Wang; Ke-Dong Ma; Yan-Wei Wang; Hui-Min Wang; Yan-Bin Li; Shan Zhou; Xiao-Rong Chen; De-Long Kong; Xiang Guo; Ming-Xiong He; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2016)

Floral Transcriptome Analyses of Four Paphiopedilum Orchids with Distinct Flowering Behaviors and Development of Simple Sequence Repeat Markers - Dong-Mei Li; Wei Wu; Di Zhang; Xiao-Rong Liu; Xiao-Fei Liu; Yi-Jian Lin (Plant Molecular Biology Reporter, 2015)

An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2015)
IRF-1, a kind of transcription factor, is expressed in many cell types, except in early embryonal cells. IRF-1 has played an essential role in various physiological and pathological processes, including tumor immune surveillance, viral infection, development of immunity system and pro-inflammatory injury. However, the expression and function of IRF-1 in spinal cord injury (SCI) are still unknown. In this study, we have performed an acute SCI model in adult rats and investigated the dynamic changes of IRF-1 expression in the spinal cord. Western blot have shown that IRF-1 protein levels gradually increased, reaching a peak at day 3 and then gradually declined to a normal level at day 14 after SCI. Double immunofluorescence staining showed that IRF-1 immunoreactivity was found in neurons, but not in astrocytes and microglia. Additionally, colocalization of IRF-1/active caspase-3 was detected in neurons. In vitro, IRF-1 depletion, by short interfering RNA, obviously decreases neuronal apoptosis. In conclusion, this is the first description of IRF-1 expression in spinal cord injury. Our results suggested that IRF-1 might play crucial roles in CNS pathophysiology after SCI.

Interlocking Intramedullary Nails in Fracture Treatment - Xiao Ouyang; Jing Rong Wang; Shi Dong Hong; Feng Xin; Lin Wang; Xiao Wei Yang; Jian Wang (Cell Biochemistry and Biophysics, 2015)

Study on the Mechanisms of Cartilage Tissue Damage Caused by Hydrogen Peroxide - Xiao Ouyang; Bo Wei; Shi Dong Hong; Jing Rong Wang; Feng Xin; Lin Wang; Xiao Wei Yang; Li Ming Wang (Cell Biochemistry and Biophysics, 2015)

Paenibacillus vini sp. nov., isolated from alcohol fermentation pit mud in Sichuan Province, China - Xiao-Rong Chen; Cheng-Bin Shao; Yan-Wei Wang; Ming-Xiong He; Ke-Dong Ma; Hui-Min Wang; De-Long Kong; Xiang Guo; Yi-Qing Zhou; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2015)

Association analyses of FGFR2 gene polymorphisms with femoral neck bone mineral density in Chinese Han population - Shan-Shan Dong; Tie-Lin Yang; Han Yan; Zheng-Qin Rong; Jia-Bin Chen; Ruo-Han Hao; Xiao-Feng Chen; Yan Guo (Molecular Genetics and Genomics, 2015)

Identification of a new maize inflorescence meristem mutant and association analysis using SLAF-seq method - Chao Xia; Li-li Chen; Ting-zhao Rong; Rui Li; Yong Xiang; Peng Wang; Chun-hua Liu; Xiao-qiu Dong; Bing Liu; Dan Zhao; Ru-jun Wei; Hai Lan (Euphytica, 2015)

Tree architecture varies with forest succession in evergreen broad-leaved forests in Eastern China - Xiao-Dong Yang; En-Rong Yan; Scott X. Chang; Liang-Jun Da; Xi-Hua Wang (Trees, 2015)

De novo analysis of the Tenebrio molitor (Coleoptera: Tenebrionidae) transcriptome and identification of putative glutathione S-transferase genes - Su Liu; Xiao-Xiao Shi; Yan-Dong Jiang; Zi-Jie Zhu; Ping Qian; Min-Jing Zhang; Hang Yu; Qing-Zi Zhu; Zhong-Jun Gong; Zeng-Rong Zhu (Applied Entomology and Zoology, 2015)

Humanin attenuates Alzheimer-like cognitive deficits and pathological changes induced by amyloid β-peptide in rats - Gao-Shang Chai; Dong-Xiao Duan; Rong-Hong Ma; Jian-Ying Shen; Hong-Lian Li; Zhi-Wei Ma; Yu Luo; Lu Wang; Xin-Hua Qi; Qun Wang; Jian-Zhi Wang; Zelan Wei; et al. (Neuroscience Bulletin, 2014)

Analysis of DNA methylation of perennial ryegrass under drought using the methylation-sensitive amplification polymorphism (MSAP) technique - Xiao-Mei Tang; Xiang Tao; Yan Wang; Dong-Wei Ma; Dan Li; Hong Yang; Xin-Rong Ma (Molecular Genetics and Genomics, 2014)

First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2014)

Research and experimental testing of a new kind electrokinetic logging tool - Feng-Bo Li; Xiao-Dong Ju; Wen-Xiao Qiao; Jun-Qiang Lu; Bai-Rong Men (Applied Geophysics, 2014)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

Potential Effects of Mina53 on Tumor Growth in Human Pancreatic Cancer - Xiao-ping Tan; Wei-guo Dong; Qing Zhang; Zi-rong Yang; Xiao-fei Lei; Ming-hua Ai (Cell Biochemistry and Biophysics, 2014)

IFNG polymorphisms are associated with tuberculosis in Han Chinese pediatric female population - Chen Shen; Wei-Wei Jiao; Wei-Xing Feng; Xi-Rong Wu; Jing Xiao; Qing Miao; Lin Sun; Bin-Bin Wang; Jing Wang; Fang Liu; Dan Shen; A-Dong Shen (Molecular Biology Reports, 2013)

A Novel Peptide Can Mimic Extracellular Fibrinogen-Binding Protein to Block the Activation of Complement System - Ya-ping Gao; Jie Dong; Xin Zhang; Yu Liu; Qiang Lu; Jian-nan Feng; Xiao-rong Tan; Guang Yang (Cell Biochemistry and Biophysics, 2013)

Role of Paraoxonase-1 in the Protection of Hydrogen Sulfide-Donating Sildenafil (ACS6) Against Homocysteine-Induced Neurotoxicity - Xiao-Qing Tang; Rong-Qian Chen; Ling Dong; Yan-Kai Ren; Piero Del Soldato; Anna Sparatore; Duan-Fang Liao (Journal of Molecular Neuroscience, 2013)

Oxidative Parameters in the Rat Brain of Chronic Mild Stress Model for Depression: Relation to Anhedonia-Like Responses - Chao Wang; He-ming Wu; Xiao-rong Jing; Qiang Meng; Bei Liu; Hua Zhang; Guo-dong Gao (The Journal of Membrane Biology, 2012)

Neuroprotection by Silencing iNOS Expression in a 6-OHDA Model of Parkinson’s Disease - Min Li; Fu-rong Dai; Xiao-ping Du; Qi-dong Yang; Yuxiang Chen (Journal of Molecular Neuroscience, 2012)

One-Step Bulk Preparation of Calcium Carbonate Nanotubes and Its Application in Anticancer Drug Delivery - Jing Tang; Dong-Mei Sun; Wen-Yu Qian; Rong-Rong Zhu; Xiao-Yu Sun; Wen-Rui Wang; Kun Li; Shi-Long Wang (Biological Trace Element Research, 2012)

A recessive gene controlling male sterility sensitive to short daylength/low temperature in wheat (Triticum aestivum L.) - Xiao-dong Chen; Dong-fa Sun; De-fu Rong; Jun-hua Peng; Cheng-dao Li (Journal of Zhejiang University-SCIENCE B, 2011)

Isolation of a buprofezin co-metabolizing strain of Pseudomonas sp. DFS35-4 and identification of the buprofezin transformation pathway - Kai Chen; Xiao-Mei Liu; Rong Li; Yuan Liu; Hai Hu; Shun-Peng Li; Jian-Dong Jiang (Biodegradation, 2011)

Cytosolic PrP Induces Apoptosis of Cell by Disrupting Microtubule Assembly - Xiao-Li Li; Gui-Rong Wang; Yuan-Yuan Jing; Ming-Ming Pan; Chen-Fang Dong; Rui-Min Zhou; Zhao-Yun Wang; Qi Shi; Chen Gao; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Effects of erythromycin on voriconazole pharmacokinetics and association with CYP2C19 polymorphism - Hui-Yan Shi; Jin Yan; Wen-Hui Zhu; Guo-Ping Yang; Zhi-Rong Tan; Wei-Hua Wu; Gan Zhou; Xiao-Ping Chen; Dong-Sheng Ouyang (European Journal of Clinical Pharmacology, 2010)

Diversity and Antimicrobial and Plant-Growth-Promoting Activities of Endophytic Fungi in Dendrobium loddigesii Rolfe - Xiao Mei Chen; Hai Ling Dong; Ke Xing Hu; Zhi Rong Sun; Juan Chen; Shun Xing Guo (Journal of Plant Growth Regulation, 2010)

Chemometrics-based approach to modeling quantitative composition-activity relationships for Radix Tinosporae - Shi-Kai Yan; Zhong-Ying Lin; Wei-Xing Dai; Qi-Rong Shi; Xiao-Hua Liu; Hui-Zi Jin; Wei-Dong Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2010)

Efficient production of omega-3 fatty acid desaturase (sFat-1)-transgenic pigs by somatic cell nuclear transfer - DengKe Pan; Li Zhang; YanRong Zhou; Chong Feng; Chuan Long; Xiao Liu; Rong Wan; Jian Zhang; AiXing Lin; EnQiu Dong; ShuChen Wang; HouGang Xu; et al. (Science China Life Sciences, 2010)

Cytological and RAPD data revealed genetic relationships among nine selected populations of the wild bramble species, Rubus parvifolius and R. coreanus (Rosaceae) - Xiao-rong Wang; Yuan Liu; Bi-feng Zhong; Xiao-li Dong; Qing Chen; Wu-feng Xia; Hanwu Zhang; Hao-ru Tang (Genetic Resources and Crop Evolution, 2010)

Normal Shear Stress and Vascular Smooth Muscle Cells Modulate Migration of Endothelial Cells Through Histone Deacetylase 6 Activation and Tubulin Acetylation - Yan-Hua Wang; Zhi-Qiang Yan; Ying-Xin Qi; Bin-Bin Cheng; Xiao-Dong Wang; Dan Zhao; Bao-Rong Shen; Zong-Lai Jiang (Annals of Biomedical Engineering, 2010)

Association of functional polymorphisms in MMPs genes with gastric cardia adenocarcinoma and esophageal squamous cell carcinoma in high incidence region of North China - Yan Li; Dong-lan Sun; Ya-nan Duan; Xiao-juan Zhang; Na Wang; Rong-miao Zhou; Zhi-feng Chen; Shi-jie Wang (Molecular Biology Reports, 2010)

Association of TNFAIP3 polymorphism with rheumatic heart disease in Chinese Han population - Rong Hua; Ji-bin Xu; Jiu-cun Wang; Li Zhu; bing Li; Yang Liu; Sheng-dong Huang; Li Jin; Zhi-yun Xu; Xiao-feng Wang (Immunogenetics, 2009)

Manganese-induced changes of the biochemical characteristics of the recombinant wild-type and mutant PrPs - Xiao-Li Li; Chen-Fang Dong; Gui-Rong Wang; Rui-Min Zhou; Qi Shi; Chan Tian; Chen Gao; Guo-Yong Mei; Cao Chen; Kun Xu; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2009)

Morphology and genome of Euproctis pseudoconspersa nucleopolyhedrovirus - Xu-Dong Tang; Qiang Xiao; Xiu-Cui Ma; Zeng-Rong Zhu; Chuan-Xi Zhang (Virus Genes, 2009)

No spatial memory deficit exists in Kunming mice that recently recovered from motor defects following 3-nitropropionic acid intoxication - Xiao-Min Li; Bing-Gen Zhu; Jian-Bo Ni; Chun-Yan Cao; Jie-Ping Zhang; Xu-Dong Zhao; Rong-Shen Zhu (Neuroscience Bulletin, 2009)

An investigation on the polymorphisms of two DNA repair genes and susceptibility to ESCC and GCA of high-incidence region in northern China - Na Wang; Xiu-juan Dong; Rong-miao Zhou; Wei Guo; Xiao-juan Zhang; Yan Li (Molecular Biology Reports, 2009)

Molecular interaction between prion protein and GFAP both in native and recombinant forms in vitro - Chen-Fang Dong; Xiao-Fan Wang; Xin Wang; Song Shi; Gui-Rong Wang; Bing Shan; Run An; Xiao-Li Li; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2008)

Isolation and identification of Sclerotinia stem rot causal pathogen in Arabidopsis thaliana - Ai-rong Wang; Wen-wei Lin; Xiao-ting Chen; Guo-dong Lu; Jie Zhou; Zong-hua Wang (Journal of Zhejiang University-SCIENCE B, 2008)

Depressive-like behavior in mice recently recovered from motor disorders after 3-nitropropionic acid intoxication - Xiao-Min Li; Bing-Gen Zhu; Sha Ma; Wei Zhou; Zheng Wei; Yu-Xiang Zheng; Xu-Dong Zhao; Rong-Shen Zhu (Neuroscience Bulletin, 2008)

Effect of fungal fusaric acid on the root and leaf physiology of watermelon (Citrullus lanatus) seedlings - Hong-sheng Wu; Xiao-ming Yin; Dong-yang Liu; Ning Ling; Wei Bao; Rong-rong Ying; Yi-yong Zhu; Shi-wei Guo; Qi-rong Shen (Plant and Soil, 2008)

Different expression patterns of CK2 subunits in the brains of experimental animals and patients with transmissible spongiform encephalopathies - Jian-Ming Chen; Chen Gao; Qi Shi; Bing Shan; Yan-Jun Lei; Chen-Fang Dong; Run An; Gui-Rong Wang; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Archives of Virology, 2008)

Secretion of malate and citrate from roots is related to high Al-resistance in Lespedeza bicolor - Xiao Ying Dong; Ren Fang Shen; Rong Fu Chen; Zhao Liang Zhu; Jian Feng Ma (Plant and Soil, 2008)

Timing and duration of supergene mineralization at the Xinrong manganese deposit, western Guangdong Province, South China: cryptomelane 40Ar/39Ar dating - Jian-Wei Li; Paulo Vasconcelos; Wei Zhang; Xiao-Dong Deng; Nurdan Duzgoren-Aydin; Dai-Rong Yan; Jian-Qiang Zhang; Ming-An Hu (Mineralium Deposita, 2007)

Phenolic constituents from the rhizomes of Gastrodia elata - Xiao-Dong Yang; Jie Zhu; Rong Yang; Jing-Ping Liu; Liang Li; Hong-Bin Zhang (Natural Product Research, 2007)

Genetic linkage of human height is confirmed to 9q22 and Xq24 - Yao-Zhong Liu; Peng Xiao; Yan-fang Guo; Dong-Hai Xiong; Lan-Juan Zhao; Hui Shen; Yong-Jun Liu; Volodymyr Dvornyk; Ji-Rong Long; Hong-Yi Deng; Jin-Long Li; Robert R. Recker; et al. (Human Genetics, 2006)

Tissue distribution of the secretory protein, SPLUNC1, in the human fetus - Hou-De Zhou; Song-Qin Fan; Jin Zhao; Dong-Hai Huang; Ming Zhou; Hua-Ying Liu; Zhao-Yang Zeng; Yi-Xing Yang; He Huang; Xiao-Ling Li; Shou-Rong Shen; Gui-Yuan Li (Histochemistry and Cell Biology, 2006)

Ovipositor length of threeApocrypta species: Effect on oviposition behavior and correlation with syconial thickness - Wen-Quan Zhen; Da-Wei Huang; Jin-Hua Xiao; Da-Rong Yang; Chao-Dong Zhu; Hui Xiao (Phytoparasitica, 2005)